PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE COURSE REVIEW HOREY DI KELAS IV SDN 10 SAPIRAN KOTA BUKITTINGGI - Lailatul Rahmi; Zuardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Based on previous studies, the learning process in learning Pancasila Education in class IV SDN 10 Sapiran Bukittinggi City has not been optimal so that it has an impact on low learning outcomes. This study aims to describe the improvement of student learning outcomes in Pancasila Education learning using the Course Review Horey model. This type of research is classroom action research (PTK) using qualitative and quantitative approaches. This research was conducted in two cycles, with the research procedure consisting of planning, implementation, observation, and reflection. The research data obtained was related to the learning outcomes of the Course Review Horay model. Data collection techniques were in the form of tests and non-tests. The subjects of this study were class teachers as observers or observers, researchers as practitioners or teachers, and fourth grade students of SDN 10 Sapiran, Bukittinggi City, totaling 16 people. The results showed an increase in: a) the average teaching module of cycle I is 80.5% with qualification B (Good), increased in cycle II to 94% with qualification SB (Very Good), b) the implementation of learning in the teacher aspect, cycle I is 78.36% with qualification C (Enough) increased in cycle II is 95.45% with qualification SB (Very Good) and in the aspect of students cycle I is 78.36% with qualification C (Enough) increased in cycle II is 95.45% with qualification SB (Very Good). c) The learning outcomes of students in cycle I obtained a score of 75 with qualifications C (Fair) and increased in cycle II to 85 with qualifications B (Good). Based on these results it can be concluded that the Course Revie Horey model can improve student learning outcomes in Pancasila Education subjects in class IV SDN 10 Sapiran Bukittinggi City.